Vacuum vapor migration strategy for atom–nanoparticle composite catalysts boosting bifunctional oxygen catalysis and rechargeable Zn–air batteries. Issue 6 (14th January 2022) - Zhang, Yun-Long; Dai, Yun-Kun; Liu, Bo; Gong, Xiao-Fei; Zhao, Lei; Cheng, Feng; Cai, Jia-Jun; Zhou, Qing-Yan; Liu, Bing; Wang, Zhen-Bo
Abstract : A "vacuum vapor migration strategy" is employed to successfully prepare a novel CoNi–N–C catalyst containing uniformly dispersed CoNi alloy nanoparticles as a conceptually solid–ligand coupling with atomic Co–N x –C active sites. Abstract : Reasonable design of bifunctional catalysts for oxygen reduction reactions (ORR) and oxygen evolution reactions (OER) is of great importance for the large-scale deployment of metal–air batteries. Herein, we developed a facile and scalable vacuum vapor migration strategy to successfully prepare CoNi–N–C composite catalysts for bifunctional oxygen catalysis. This unique strategy enables the gaseous nickel species to be captured and anchored by CoCN substrates and the simultaneous pyrolysis process results in the generation of ultrafine CoNi nanoparticles (NPs) coupling with atomic Co–N x –C moieties. CoNi NPs act as "solid–ligands" to modulate and activate Co–N x active sites to accelerate the oxygen catalysis kinetics, delivering a remarkable bifunctional activity of Δ E of 0.71 V, far exceeding the precious metal Pt/C + Ir/C comparisons and most reported precious metal-free catalysts. Correspondingly, the CoNi–N–C based Zn–air battery exhibits excellent cyclability for over 200 hours with high voltage efficiency. Given the easy scale-up production and unique atom–nanoparticle composite sites, this work provides some insights for the rational synthesis of high-performance bifunctional oxygen catalysts for practical applications.